Feasibility and clinical relevance of genotyping samples with low-level viremia in a cohort of HIV infected South African patients on HAART - Bangalee, Avania (My University, 2020)
Objectives: The feasibility of HIV genotyping at low-level viraemia (LLV) using an in-house assay in a South African population was assessed and the prevalence as well as the clinical relevance of drug resistance (HIVDR) in this population was determined. Methods: We conducted an observational, retrospective, cohort study on patient samples with LLV referred for routine HIVDR testing at a public sector Johannesburg laboratory from Aup•ust 2017 to October 2018. Genotyping was performed usinp• a nested RT-PCR assay. The genotyping success rate was evaluated for different viraemia categories. HIV-1 drug resistance analysis was done using Sanger sequencing and sequences were loaded onto the Stanford HIVdb genotypic resistance tool (v 8.7) for drug resistance interpretation. Results: Plasma samples from 159 HIV-I infected, treatment-experienced adults with LLV were analysed. The in-house assay performed well with an overall success rate of 78.67a (125f 159, 95% CI 71.6 — 84.3). The prevalence of drug resistance mutations in the LLV cohort was 79.2Yo (99/125, 95% CI 71.2 — 85.4) with most patients (n = 109, 68.6'7o) on a PI-based regimen at the time of genotyping. Of 125 sequences obtained, 73.67a (92/125) had *1 NRTI mutation while 70.47c (88/125) had Al NNRTI mutation. Importantly, major PI mutations including M46I and V82A were detected in 7.270 (9/125) of patients. Conclusion: Current South African virological failure guidelines may keep patients on failing regimens for longer than necessary. Our data suggests that genotyping at LLV is feasible and implementation could result in earlier identification and referral of patients requiring third - line regimens.
Thesis (MMed (Virology))--University of the Witwatersrand, Faculty of Health Sciences, 2020